The Tribal Journey : Significant for Liberal Arts Programme Students - Srivastava, Gaura (University News, 2023)
The Liberal Arts Programme is a unique opportunity for experimentation. The students enjoy the course because of several reasons, firstly, it’s outside their domain of study, yet, connected metaphorically, with allied, supportive information and directions for inquiry. Secondly, there’s always the element of unpredictability, and a likelihood of the unknown being drawn into the dialectic – which could belong to then or now or even a maybe, perhaps might someday, or never – an impossibility worth discussing anyway. Thirdly, it’s a means to connect dots and build superstructures of knowledge that can add to their visual, intellectual, and argument repertory.
ISDI